Sex-related differences and age of peak performance in breaststroke versus freestyle swimming - Wolfrum, M.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (BMC Sports Science, Medicine and Rehabilitation, 2013)
Sex-related differences in performance and in age of peak performance have been reported for freestyle swimming. However, little is known about the sex-related differences in other swimming styles. The aim of the present study was to compare performance and age of peak performance for elite men and women swimmers in breaststroke versus freestyle. Methods: Race results were analyzed for swimmers at national ranked in the Swiss high score list (during 2006 through 2010) and for international swimmers who qualified for the finals of the FINA World Swimming Championships (during 2003 through 2011). Results: The sex-related difference in swimming speed was significantly greater for freestyle than for breaststroke over 50 m, 100 m, and 200 m race distances for Swiss swimmers, but not for FINA finalists. The sex-related difference for both freestyle and breaststroke swimming speeds decreased significantly with increasing swimming distance for both groups. Race distance did not affect the age of peak performance by women in breaststroke, but age of peak performance was four years older for FINA women than for Swiss women. Men achieved peak swimming performance in breaststroke at younger ages for longer race distances, and the age of peak swimming performance was six years older for FINA men than for Swiss men. In freestyle swimming, race distance did not affect the age of peak swimming performance for Swiss women, but the age of peak swimming performance decreased with increasing race distance for Swiss men and for both sexes at the FINA World Championships. Conclusions: Results of the present study indicate that (i) sex-related differences in swimming speed were greater for freestyle than for breaststroke for swimmers at national level, but not for swimmers at international level, and (ii) both female and male swimmers achieved peak swimming speeds at younger ages in breaststroke than in freestyle. Further studies are required to better understand differences between trends at national and international levels.